Routledge handbook of media, conflict and security - Robinson, Piers; Seib, Philip M.; Frohlich, Romy (Routledge, Taylor & Francis Group, 2017)
This Handbook links the growing body of media and conflict research with the field of security studies. For scholars of security studies, this handbook will provide a key point of reference for state of the art scholarship concerning the media-security nexus; for scholars of communication and media studies, the handbook will provide a comprehensive mapping of the media-conflict field.